Evaluation of the Association between Serum Levels of Vitamin D and Benign Paroxysmal Positional Vertigo (BPPV): A Case-Control Study - Imani, Adel; Khajavi, Mahdi; Ghazizadeh Hashemi , Amir Hossain; Bazgir, Narges; Davodi, Farzin; Kordjazi, Mohammadsmaeil; Mohammadi, Mahya (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Benign paroxysmal positional vertigo (BPV) is the most common cause of the high prevalence of vertigo. Today, BPV is caused by the separation of autochthonous particles from the macular atrial. As a result, these particles float in a semicircular canal and change position by gravity. The majority of vertigo causes arise from the inner ear. Aim: This study aims to measure the vitamin D level in patients with BPPV who visited Loghman Hakim Hospital clinics and compare the results with controls. Methods: This comparative study evaluated the effect of vitamin D on reducing BPV. Demographic information of patients was collected through interviews. The physical examinations were recorded through a questionnaire. For the group with BPPV, we did the Epley maneuver and measured the vitamin D level. We compared the vitamin D levels of these patients with the matched control group. Results: In this study, 148 patients were evaluated. Sixty-three patients were male, and 85 patients were female. All case and control patients were tested for vitamin D levels. Of 93 patients with benign vertigo, 39 (41.9%) patients had normal vitamin D levels, and 54(58.1%) patients had below normal. In the control group, 43 (78.2%) patients had normal vitamin D, and 12 (21.8%) patients had less than normal. There was a statistically significant difference between the two groups. Conclusion: The present study indicated that BPV was more prevalent in people with vitamin D deficiency, and vitamin D treatment could effectively control and reduce the prevalence of this disease.